Structure and method for testing curing degree of ultraviolet curing adhesive for optical fiber ring

Through the method of posted transparent tape on the fiber ring sample and filled UV curing glue in the ring case for ultraviolet light irradiation, the problem of complex time consumption test of the optical ring curing curing test in the existing technologies has been solved. The precise test reduces R & D costs.

CN119354800APending Publication Date: 2025-01-24CHONGQING HUAYU ELECTRIC GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411492303.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively test the curing degree of the two layers of ultraviolet curing glue inside and outside the fiber ring, and the traditional methods are complex and time-consuming, which can easily damage the fiber ring and increase R&D costs.

Method used

Design a solidification test structure and method of ultraviolet curing glue with an optical fiber ring. By posting transparent tape on the fiber -fiber ring sample, ultraviolet gum is filled with ultraviolet light in the ring case for ultraviolet light. Essence

Benefits of technology

The solidification of ultraviolet curing glue on the fiber ring on the fiber ring is achieved quickly, avoiding damage to the fiber ring, simplifying operations, reducing R & D costs, and improving test accuracy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119354800A_ABST
    Figure CN119354800A_ABST
Patent Text Reader

Abstract

The invention discloses a curing degree testing structure and testing method of ultraviolet curing glue for an optical fiber ring, the testing structure comprises an optical fiber ring sample and a curing tool, the curing tool comprises a bottom plate and a cover plate which are horizontally arranged, the center of the upper surface of the bottom plate is vertically provided with a cylindrical boss, the boss is sleeved with an annular sleeve, and the inner side of the annular sleeve is tightly attached to the boss; the optical fiber ring sample is arranged on the annular sleeve in a sleeving manner, transparent adhesive tapes are arranged on an inner ring and an outer ring of the optical fiber ring sample, the transparent adhesive tapes completely cover the inner ring and the outer ring of the optical fiber ring sample, and a gap of 1-2mm is formed between the optical fiber ring sample and the annular sleeve; the center of the cover plate is provided with concave cavities corresponding to the bosses and the annular sleeves in a one-to-one mode, and the cover plate is arranged on the bottom plate in a buckled mode and fixedly connected with the bottom plate through a connecting piece. The device is convenient to operate, can quickly and effectively sample on the optical fiber ring, and improves the curing degree test efficiency and precision of the ultraviolet curing adhesive, so that the precision and stability of the optical fiber ring assembled on the optical fiber gyroscope are ensured, and meanwhile, the research and development cost can be effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of navigation systems, relates to a fiber optic gyroscope, and in particular to a curing degree test structure and a test method of ultraviolet curing glue for an optical fiber ring. Background Art

[0002] Fiber optic gyroscope is a high-precision inertial sensor based on the Sagnac effect. It has excellent impact resistance, long life, low power consumption, high sensitivity and other advantages. It has been widely used in weapons and equipment, sea, land, air, space, and other fields that require measuring the angular motion and orientation of objects.

[0003] The fiber optic ring is one of the sensitive devices at the core of the fiber optic gyroscope. The fiber optic ring is a photocurable composite material formed by coating a layer of UV curing glue on the optical fiber of the wound fiber optic coil to bond and fix it. The fiber optic coil and the UV glue are cured by UV light to form a whole. Common UV curing glues are generally acrylic, vinyl and epoxy. When the photoinitiator is exposed to UV light, it forms free radicals or cations, which then initiate the polymerization reaction of active monomers, and finally form a three-dimensional cross-linked network and insoluble thermosetting resin. The degree of cross-linking of the resin is also called the degree of curing, which refers to the conversion rate of the curing reaction. The Young's modulus, hardness, tensile strength, expansion performance, heat resistance, and aging resistance of the resin are closely related to the degree of curing.

[0004] If the UV curing adhesive is not fully cured when the UV light is insufficient, it is easy to have substandard mechanical properties, easy to be damaged, and weak ability to fix the optical fiber. In the case of excessive UV light exposure, the UV curing adhesive is prone to aging and yellowing. In severe cases, it may even degrade and cause a significant decline in performance. It is worth noting that the wound optical fiber coil has a certain thickness and the UV light penetration ability is limited, which weakens the ability of the UV light to penetrate into the inner layer of the optical fiber coil and activate the inner layer photoinitiator. This will cause the degree of curing of the two layers of UV curing adhesive inside and outside the optical fiber ring to be inconsistent, which will lead to uneven stress distribution inside the optical fiber ring and affect the accuracy and stability of the optical fiber gyroscope. At present, optical fibers and UV curing adhesives have different manufacturers and models, and optical fiber coils for different purposes have different sizes and thicknesses. The UV lamp power, irradiation time and distance involved in the curing process will affect the curing degree of the UV curing adhesive in the optical fiber ring after curing.

[0005] At present, there are two methods to test the curing degree of the two layers of UV curing adhesive inside and outside the optical fiber ring:

[0006] The first method is to directly study the curing degree of the UV-curing adhesive, that is, to peel off the cured UV-curing adhesive on the inner and outer layers of the optical fiber ring for curing degree testing. This method is not only difficult, but also damages the optical fiber ring.

[0007] The second method is to indirectly judge the curing degree of the UV-curing adhesive, that is, to assemble a fiber optic ring on a fiber optic gyroscope to test the performance of the fiber optic gyroscope, and indirectly judge whether the curing degree of the UV-curing adhesive is optimal. Each time the curing conditions are changed, a new fiber optic ring needs to be wound for testing. This is not only complicated and time-consuming, but also unable to effectively test the curing degree of the UV-curing adhesive, and will also increase research and development costs. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a curing degree test structure and test method for ultraviolet curing glue for optical fiber rings. The present invention is easy to operate, can quickly and effectively take samples on the optical fiber ring, and improve the efficiency and accuracy of the curing degree test of the ultraviolet curing glue, which is beneficial to ensure the accuracy and stability of the optical fiber ring after being assembled on the optical fiber gyroscope, and can also effectively reduce the research and development costs.

[0009] The technical solution of the present invention is achieved in this way:

[0010] A curing degree test structure for ultraviolet curing glue for optical fiber rings, comprising an optical fiber ring sample and a curing tool, the curing tool comprising a horizontally arranged base plate and a cover plate, a cylindrical boss is vertically arranged at the center of the upper surface of the base plate, an annular sleeve is sleeved on the boss, the inner side of the annular sleeve is tightly fitted with the boss, the optical fiber ring sample is sleeved on the annular sleeve, and the inner ring and outer ring of the optical fiber ring sample are both provided with transparent tape, and the transparent tape fully covers the inner ring and outer ring of the optical fiber ring sample, and at the same time, there is a gap of 1 to 2 mm between the optical fiber ring sample and the annular sleeve; a concave cavity corresponding to the boss and the annular sleeve is arranged in the center of the cover plate, the cover plate is buckled on the base plate and fixed to the base plate through a connector.

[0011] The present invention also provides a method for testing the curing degree of ultraviolet curing adhesive for optical fiber rings, which specifically comprises the following steps:

[0012] S1: Assemble the fiber optic ring sample on the curing tooling, the curing tooling includes a horizontally arranged bottom plate and a cover plate, the center of the upper surface of the bottom plate is vertically provided with a cylindrical boss, the boss is sleeved with an annular sleeve, the inner side of the annular sleeve is tightly fitted with the boss, and the center of the cover plate is provided with a concave cavity corresponding to the boss and the annular sleeve; when assembling the fiber optic ring sample, firstly paste transparent tape on the inner ring and outer ring of the fiber optic ring sample, so that the transparent tape fully covers the inner ring and outer ring of the fiber optic ring sample; then sleeve the fiber optic ring sample on the annular sleeve, and there is a gap of 1 to 2 mm between the fiber optic ring sample and the annular sleeve; then fill the gap with ultraviolet curing glue, and at the same time, evenly apply a layer of ultraviolet curing glue on the transparent tape of the outer ring of the fiber optic ring sample, and then assemble the cover plate;

[0013] S2: Place the curing device of the optical fiber ring sample assembled in S1 in a UV curing box and cure it under UV light;

[0014] S3: After the curing is completed, the UV curing adhesive of the inner layer and the outer layer of the optical fiber ring sample is taken out along the transparent tape as a test sample, and then the curing degree of the test samples of the inner layer and the outer layer of the optical fiber ring sample is tested respectively.

[0015] Furthermore, the annular sleeve is made of polytetrafluoroethylene plastic or a polytetrafluoroethylene coating is provided on the outer side of the annular sleeve.

[0016] Furthermore, the transparent tape is a polypropylene film tape.

[0017] Furthermore, in step S3, the curing degree of the UV curing adhesive is tested by using a Soxhlet extraction method or a solvent immersion method.

[0018] Furthermore, the specific steps of using the Soxhlet extraction method to test the curing degree of the UV curing adhesive are as follows:

[0019] (1) Weigh 1 g of the test sample, cut it into pieces, and place it in an oven at 80-100°C to remove water. Record its mass M. 1 ;

[0020] (2) Place the dried test sample in a Soxhlet extractor containing an organic solvent for 48 hours, then take out the sample and place it in a drying oven to dry it to remove the organic solvent until constant weight is recorded. 2 , so the curing degree of UV curing adhesive is M 2 / M 1 ×100%.

[0021] Furthermore, the specific steps of testing the curing degree of the UV curing adhesive by the solvent immersion method are as follows:

[0022] (1) Weigh 1 g of the test sample, cut it into pieces, and place it in an oven at 80-100°C to remove water. Record its mass M. 1 ;

[0023] (2) Soak the dried test sample in an organic solvent for 72 hours, then take out the sample and dry it in a drying oven to remove the organic solvent until constant weight is achieved. Record the mass M at this time. 2 , so the curing degree of UV curing adhesive is M 2 / M 1 ×100%.

[0024] Furthermore, the organic solvent is acetone, chloroform or toluene.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention posts transparent tape on the inner and outer rings of the optical fiber ring sample, and at the same time sets an annular sleeve with high halo properties on the inner side of the optical fiber ring sample. The inner and outer layers of the ultraviolet curing adhesive of the optical fiber ring sample can be easily removed after curing, and will not cause damage to the optical ring. At the same time, the whole process is simple to operate and can effectively ensure the accuracy of the curing degree test.

[0027] 2. The fiber optic ring sample of the present invention can be reused to study the curing degree of the UV curing adhesive under different curing conditions, thereby effectively reducing the research and development cost, and at the same time facilitating the acquisition of the best curing process conditions and ensuring the curing degree accuracy of the UV curing adhesive, thereby facilitating the improvement of the accuracy and stability of the fiber optic ring after being assembled on the fiber optic gyroscope. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 -Structural schematic diagram of the curing degree test structure of the present invention.

[0029] Wherein: 1-bottom plate; 2-boss; 3-annular sleeve; 4-gap; 5-inner transparent tape; 6-optical fiber ring sample; 7-outer transparent tape; 8-cover plate. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0031] See also Figure 1 , a curing degree test structure of ultraviolet curing glue for optical fiber ring, including an optical fiber ring sample 6 and a curing tool, the curing tool including a horizontally arranged bottom plate 1 and a cover plate 8, a cylindrical boss 2 is vertically arranged at the center of the upper surface of the bottom plate 1, an annular sleeve 3 is sleeved on the boss 2, the inner side of the annular sleeve 3 is tightly fitted with the boss 2, the optical fiber ring sample 6 is sleeved on the annular sleeve 3, and the inner ring and the outer ring of the optical fiber ring sample 6 are both provided with transparent tape, the inner ring corresponds to the inner layer of transparent tape 5, the outer ring corresponds to the outer layer of transparent tape 7, and the transparent tape fully covers the inner ring and the outer ring of the optical fiber ring sample 6, and there is a 1-2mm gap 4 between the optical fiber ring sample 6 and the annular sleeve 3; the center of the cover plate 8 is provided with a concave cavity corresponding to the boss 2 and the annular sleeve 3, the cover plate 8 is buckled on the bottom plate 1 and is connected and fixed to the bottom plate 1 through a connecting piece.

[0032] A method for testing the curing degree of ultraviolet curing adhesive for optical fiber rings specifically comprises the following steps:

[0033] S1: See Figure 1, assemble the optical fiber ring sample 6 on the curing tooling, the curing tooling includes a horizontally arranged bottom plate 1 and a cover plate 8, a cylindrical boss 2 is vertically provided at the center of the upper surface of the bottom plate 1, an annular sleeve 3 is sleeved on the boss 2, the inner side of the annular sleeve 3 is tightly fitted with the boss 2, and a concave cavity corresponding to the boss 2 and the annular sleeve 3 is provided in the center of the cover plate 8; when assembling the optical fiber ring sample 6, firstly paste transparent tape on the inner ring and outer ring of the optical fiber ring sample 6, the inner ring corresponds to the inner layer of transparent tape 5, and the outer ring corresponds to the outer layer of transparent tape 7, so that the transparent tape fully covers the inner ring and outer ring of the optical fiber ring sample 6; then the optical fiber ring sample 6 is sleeved on the annular sleeve 3, and at the same time, there is a 1-2mm gap 4 between the optical fiber ring sample 6 and the annular sleeve 3; then fill the gap 4 with ultraviolet curing glue, and at the same time, evenly apply a layer of ultraviolet curing glue on the outer layer of transparent tape 7 of the outer ring of the optical fiber ring sample 6, and then assemble the cover plate 8.

[0034] In actual application, the cover plate and the base plate are provided with corresponding connection holes, so that after the optical fiber ring sample is assembled, the cover plate can be buckled on the base plate, and the cover plate and the base plate can be connected to form a whole through the connector.

[0035] S2: Place the curing device of the optical fiber ring sample 6 assembled in S1 in a UV curing box and cure it under UV light;

[0036] S3: After the curing is completed, the UV curing adhesive of the inner layer and the outer layer of the optical fiber ring sample is taken out along the transparent tape as a test sample, and then the curing degree of the test samples of the inner layer and the outer layer of the optical fiber ring sample is tested respectively.

[0037] The annular sleeve here can be made of a material with high smoothness and non-stickiness to the UV curing adhesive, and the transparent tape can be made of a material that does not affect the transmission of UV light and has a weaker bonding force with the cured UV curing adhesive. In this way, after the UV curing adhesive of the outer and inner layers of the optical fiber ring sample is cured, the cured optical fiber ring can be easily removed from the curing tooling, and the UV curing adhesive of the inner and outer layers of the optical fiber ring sample can also be easily removed from the transparent tape, and then the UV curing adhesive of the inner and outer layers can be tested for curing degree. The whole process is simple to operate, will not cause damage to the optical fiber ring, and can effectively ensure the accuracy of the curing degree test.

[0038] In addition, after cleaning the excess UV-curing glue and transparent tape outside the fiber optic ring sample itself, the fiber optic ring sample can be reused to study the curing degree of the UV-curing glue under different curing conditions, thereby effectively reducing the research and development cost and facilitating the acquisition of the best curing process conditions to ensure the accuracy of the UV-curing glue curing degree, which is beneficial to improving the accuracy and stability of the fiber optic ring after being assembled on the fiber optic gyroscope.

[0039] When applying, when testing the curing degree of UV curing adhesive for optical fiber rings of different specifications, it is sufficient to use optical fiber ring samples of corresponding specifications to conduct the test experiment.

[0040] In specific implementation, the annular sleeve 3 is made of polytetrafluoroethylene plastic or a polytetrafluoroethylene coating is provided on the outer side of the annular sleeve 3. The transparent tape is a polypropylene film tape.

[0041] In specific implementation, in step S3, the curing degree of the UV curing adhesive is tested by using a Soxhlet extraction method or a solvent immersion method.

[0042] In specific implementation, the specific steps of using the Soxhlet extraction method to test the curing degree of the UV curing adhesive are as follows:

[0043] (1) Weigh 1 g of the test sample, cut it into pieces, and place it in an oven at 80-100°C to remove water. Record its mass M. 1 ;

[0044] (2) Place the dried test sample in a Soxhlet extractor containing an organic solvent for 48 hours, then take out the sample and place it in a drying oven to dry it to remove the organic solvent until constant weight is recorded. 2 , so the curing degree of UV curing adhesive is (M 2 / M 1 )×100%.

[0045] In specific implementation, the specific steps of testing the curing degree of UV curing adhesive by solvent immersion method are as follows:

[0046] (1) Weigh 1 g of the test sample, cut it into pieces, and place it in an oven at 80-100°C to remove water. Record its mass M. 1 ;

[0047] (2) Soak the dried test sample in an organic solvent for 72 hours, then take out the sample and dry it in a drying oven to remove the organic solvent until constant weight is achieved. Record the mass M at this time. 2 , so the curing degree of UV curing adhesive is (M 2 / M 1 )×100%.

[0048] In a specific implementation, the organic solvent is acetone, chloroform or toluene.

[0049] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A curing degree test structure for ultraviolet curing adhesive for optical fiber ring, characterized in that: It includes a fiber optic ring sample and a curing tooling, the curing tooling includes a horizontally arranged bottom plate and a cover plate, a cylindrical boss is vertically arranged at the center of the upper surface of the bottom plate, an annular sleeve is sleeved on the boss, the inner side of the annular sleeve is tightly fitted with the boss, the fiber optic ring sample is sleeved on the annular sleeve, and the inner ring and outer ring of the fiber optic ring sample are both provided with transparent tape, and the transparent tape fully covers the inner ring and outer ring of the fiber optic ring sample, and there is a 1-2 mm gap between the fiber optic ring sample and the annular sleeve; a concave cavity corresponding to the boss and the annular sleeve is arranged in the center of the cover plate, the cover plate is buckled on the bottom plate and is connected and fixed to the bottom plate through a connector.

2. A method for testing the curing degree of ultraviolet curing adhesive for optical fiber ring, characterized in that: The specific steps include: S1: Assemble the fiber optic ring sample on the curing tooling, the curing tooling includes a horizontally arranged bottom plate and a cover plate, the center of the upper surface of the bottom plate is vertically provided with a cylindrical boss, the boss is sleeved with an annular sleeve, the inner side of the annular sleeve is tightly fitted with the boss, and the center of the cover plate is provided with a concave cavity corresponding to the boss and the annular sleeve; when assembling the fiber optic ring sample, firstly paste transparent tape on the inner ring and outer ring of the fiber optic ring sample, so that the transparent tape fully covers the inner ring and outer ring of the fiber optic ring sample; then sleeve the fiber optic ring sample on the annular sleeve, and there is a gap of 1-2 mm between the fiber optic ring sample and the annular sleeve; then fill the gap with ultraviolet curing glue, and at the same time, evenly apply a layer of ultraviolet curing glue on the transparent tape of the outer ring of the fiber optic ring sample, and then assemble the cover plate; S2: Place the curing device of the optical fiber ring sample assembled in S1 in a UV curing box and cure it under UV light; S3: After the curing is completed, the UV curing adhesive of the inner layer and the outer layer of the optical fiber ring sample is taken out along the transparent tape as a test sample, and then the curing degree of the test samples of the inner layer and the outer layer of the optical fiber ring sample is tested respectively.

3. The method for testing the curing degree of a UV curing adhesive for an optical fiber ring according to claim 2, characterized in that: The annular sleeve is made of polytetrafluoroethylene plastic or a polytetrafluoroethylene coating is arranged on the outer side of the annular sleeve.

4. The method for testing the curing degree of a UV curing adhesive for an optical fiber ring according to claim 2, characterized in that: The transparent tape is a polypropylene film tape.

5. The method for testing the curing degree of a UV curing adhesive for an optical fiber ring according to claim 2, characterized in that: In step S3, the curing degree of the UV curing adhesive is tested by using a Soxhlet extraction method or a solvent immersion method.

6. The method for testing the curing degree of a UV curing adhesive for an optical fiber ring according to claim 5, characterized in that: The specific steps of using the Soxhlet extraction method to test the curing degree of UV curing adhesive are as follows: (1) Weigh 1 g of the test sample, cut it into pieces, and place it in an oven at 80-100 °C to remove water. Record its mass M1. (2) The dried test sample is placed in a Soxhlet extractor containing an organic solvent for 48 h, then the sample is taken out and placed in a drying oven for drying to remove the organic solvent until constant weight is achieved. The mass M2 at this time is recorded. Therefore, the degree of curing of the UV-curing adhesive is M2 / M1×100%.

7. The method for testing the curing degree of a UV curing adhesive for an optical fiber ring according to claim 5, characterized in that: The specific steps for testing the curing degree of UV curing adhesive by solvent immersion method are as follows: (1) Weigh 1 g of the test sample, cut it into pieces, and place it in an oven at 80-100 °C to remove water. Record its mass M1. (2) Soak the dried test sample in an organic solvent for 72 h, then take out the sample and dry it in a drying oven to remove the organic solvent until constant weight is reached. Record the mass M2 at this time. Therefore, the degree of curing of the UV-curing adhesive is M2 / M1×100%.

8. A method for testing the curing degree of a UV curing adhesive for an optical fiber ring according to claim 6 or 7, characterized in that: The organic solvent is acetone, chloroform or toluene.